Enhancing Photocatalytic Efficiency and Hydrogen Production Through Oxygen-Defective G-C3n4/Fe2o3 Composites - Radhalayam, D (ELSEVIER SCIENCE SA, 2025)
Photocatalytic hydrogen production and organic pollutant degradation offer promising solutions to global energy and environmental challenges. In this work, we report a facile thermal pyrolysis synthesis of an oxygen-deficient g-C3N4/Fe2O3 (CN/FeO) composite, which exhibits superior photocatalytic performance. The optimized CN/FeO-2 sample achieved 89.9 % degradation efficiency for crystal violet (CV) dye and a hydrogen evolution rate of 423 mu mol g-1 h-1, which are 1.4 and 2.92 times higher than pristine g-C3N4, respectively. The enhanced activity is attributed to improved visible-light absorption, increased surface area, and efficient charge separation induced by oxygen vacancies. Further enhancement was realized by Pt loading, yielding a 6.2-fold increase in H2pro-duction. Structural, optical, and electrochemical analyses-including PL, EIS, and EPR-confirmed reduced electron-hole recombination and enhanced interfacial charge transfer. The composite also demonstrated good stability and recyclability, making it a promising candidate for solar-driven photocatalytic applications.